ANALISIS PENGARUH CELEBRITY ENDORSEMENT, KUALITAS PRODUK DAN PACKAGING TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS PADA PRODUK SKINCARE KLARITY) - Audy Maudya; Muhammad Ichwan Hamzah (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2022)
The purpose of this study to determine the effect of celebrity endorsement, product quality, and packaging on purchasing decisions for Klarity skincare products. This study was conducted on consumers who use Klarity skincare products. This research was conducted using quantitative methods and descriptive studies through questionnaires from the population of consumers of Klarity skincare products with a sample of 87 respondents, using a likert measurement scale equipped with various data collection techniques. The test was carried out through the multivariate Structural Equation Modeling (SEM) technique to determine the relationship between the X variable and the Y variable. The results of this study found that the celebrity endorsement variable has a significant effect on purchasing decisions. Product quality variable has no significant effect on purchasing decisions. And the packaging variable has a significant effect on purchasing decisions.